FAKTOR PENENTU KESUKSESAN SISTEM INFORMASI DI KANTOR PELAYANAN TERPADU KABUPATEN BANGKA - , Iswandi ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Nowadays many organizations Information Systems as an accelerator for business, to increase organizational efficiency and effectiveness in productivity, also in creating a competitive advance. Information Systems need to be designed with care to ensure the success of its application, and in the end ensuring the overall success of the Information System itself. But what factors influence the success of an Information System? Other than the Information System itself, there are individual factors to validate the success of an Information System. This is the main concern of the research that the researcher is performing upon the Combined Rapid Response Unit (CRRU) or âKantor Pelayanan Terpaduâ at the County of Bangka. The information System at the core of this research is the Information System at the Combined Rapid Response Unit in Bangka County, The system is aimed at improving the quality of public service and give a wider access to the people to receive service and the construction of quality public services which is fast, inexpensive, transparent, true and within the reach of the people. In this research, the researcher tries to develop the successful information system model by Delone dan Mclean (2003) combined with Technology Acceptance Model (TAM) Davis (1989) model. In this research model, the construction intention to use and construction use on Delone and Mclean model is substituted with the construction perceived usefulness, behavioral intention to use, and actual technology use of TAM model. Of thirteen hypothesis tested, there are five rejected hypothesis which are information quality, system quality, and service quality aginst the user satisfaction, information quality against the usefulness, and actual technology use against the benefit, while there are eight accepted hypothesis which are system quality and service quality against the usefulness, usefulness aganist the behavioral intention to use and user satisfaction, behavioral intention to use against the actual technology use, user satisfaction agains the behavioral intention to use and benefit, as well as actual technology use against the user satisfaction.